Investigating the impact of COVID-19 lockdown on pharmaceutical education in Saudi Arabia – A call for a remote teaching contingency strategy - Abdulmalik Alqurshi (Saudi Pharmaceutical Journal, 2020)
Background: COVID-19 lockdown has forced pharmacy education to be conducted remotely for approximately half of the second semester in the year 2019/2020. This sudden shift to distance learning has put the pharmacy education system through an extraordinary experience that may impact its future. Objective: To investigate the effect emergency remote teaching has had on pharmacy education in Saudi Arabia, and to provide recommendations that may help set in place a contingency strategy. Methods: Two cross-sectional Likert-scale based questionnaires targeted at students and teachers separately, designed to explore stakeholders' satisfaction in three areas of emergency distance teaching/learning: The use of virtual classrooms, completion of course learning outcomes (CLOs) and assessment via alternative methods during the COVID-19 lockdown period. Furthermore, phone interviews were conducted with teachers and students to discuss results from both questionnaires for further clarity on teacher and student views. Results: Over 700 pharmacy students, from 19 different local colleges, and 74 faculty members from 10 different local colleges have participated in this study. While it was challenging for the majority of teachers (>60%) to delivery complex scientific concepts over virtual classrooms, >35% of students and 60% of teachers have expressed concerns on the lack of student–student and student–teacher interactions. A factor that has shown a significantly negative correlation with student overall satisfaction (p < 0.01). Emergency remote teaching has forced teachers to alternative assessment methods, which the majority (70%) believe had a positive effect on students' overall skills. Almost half of students (45%) were concerned by the lack of guidance accompanied by unfamiliar methods of assessments. Conclusions: Based on statistically analysed results from cross sectional Likert-scale questionnaires aimed at stakeholders of pharmaceutical education, this study concludes with a number of recommendations that may help pharmacy colleges seize this unique opportunity to further enhance the quality of pharmacy education in Saudi Arabia.